2020
DOI: 10.36497/jri.v40i3.115
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence and the Susceptibility of the Elderly to Coronavirus Disease 2019 (COVID-19)

Abstract: A new disease caused by a newly-found coronavirus, known as Coronavirus Disease 2019 (COVID-19), has been declared as a pandemic by World Health Organization (WHO). This new disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The outbreak started in late December of 2019 and it did not take a long time until it spread to more than 200 countries in the world with over 4 million confirmed cases to date. The number keeps skyrocketing as day passes, followed by the increasing number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Research studies worldwide have shown age to be a key demographic factor and a consistent reliable indicator of an individual's likelihood of passing away due to the disease. In a large cohort study involving 2226 Spanish patients, it was reported the death rate among patients under 40 years old, between 40-49 years and 50-59 years to be 0.5%, 1.5%, and 3.8% respectively (13). This probably is due to a weakened immune system in the elderly and aged people or more likely due to a cytokine storm on exposure to COVID-19 (14).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Research studies worldwide have shown age to be a key demographic factor and a consistent reliable indicator of an individual's likelihood of passing away due to the disease. In a large cohort study involving 2226 Spanish patients, it was reported the death rate among patients under 40 years old, between 40-49 years and 50-59 years to be 0.5%, 1.5%, and 3.8% respectively (13). This probably is due to a weakened immune system in the elderly and aged people or more likely due to a cytokine storm on exposure to COVID-19 (14).…”
Section: Discussionmentioning
confidence: 98%
“…Immunosenescence is the process by which people's immune systems gradually weaken as they get older. Studies also show that immunosenescence in elderly people makes them more likely to be susceptible to infections of the respiratory tract as a consequence of compromised immune system leading to decreased mucociliary clearance, lowered mucosal barrier, or the presence of respiratory inflammation brought on by pathogenic microorganisms (13).…”
Section: Discussionmentioning
confidence: 99%
“…Immunosenescence and comorbidities in the elderly (hypertension, diabetes, cardiovascular disease, chronic lung disease, and cancer) also significantly increase mortality in this population. 2 The immune system plays a very important role in protecting the body from viral infections. The immune system is all the mechanisms used by the body to maintain the integrity of the body in order to protect the body from possible dangers posed by microorganisms in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the therapeutic targets developed for cases of viral infection is immunomodulators. 2 Pegagan embun (Hydrocotyle sibthorpioides Lam.) is known to contain flavonoid compounds which are thought to have immunomodulatory activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation